Characteristics of Party autonomy in a Transnational Electronic Consumer Contract - Moh. Ali; Agus Yudha Hernoko (Universitas Airlangga, 2019)
International contracts involving legal subjects between countries will affect the law chosen by the parties. Electronic contracts are different than conventional contracts in general. Prominent characteristics includevirtual, paperless and borderless. Determination of legal choices cannot be made with a link-point approach that is generally applicable to conventional transactions. The typical e-commerce characteristics should be special treatment for special contracts. The virtual nature that knows no national borders is difficult to determine in which country the legal event takes place. Paperless nature often overrides accuracy in transactions, especially with regard to legal choice clauses and forum choices.In addition, another character is that electronic transactions are made in standard form and are arranged for the purpose of take or leave it. Generally, business actors have determined the choice of law and the choice of the forum. Electronic contracts place consumers in a weak bargaining position (the weaker party). There are active limitations in determining the legal choice clause, causing consumers not to have an unequal bargaining power, giving rise to a fundamental paradigm shift in the principle of freedom of contract from